2015
DOI: 10.5539/ies.v8n6p32
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Management and Performance Framework for Research University in Malaysia

Abstract: Institutions of Higher Learning (IHL) in Malaysia are recognized as the core of new innovation development. This paper empirically studies one of IHLs in Malaysia with the objectives to gauge the perceived important level of success factors for innovation management, and to examine the relationship between innovation management success factors versus innovation performance. Descriptive statistical analysis and Pearson correlation test are used to validate the preliminary research framework. Finding from the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…Therefore, the likelihood of failure would appear to be considered as a deterrent, inhibiting entrepreneurs from initiating new ventures. Studies on entrepreneurship have reported that tolerance of failure promotes innovation and creativity, enabling the organization to take daring moves (Kowang et al 2015). In the Israeli context, senior managers in its high-tech industry, as well as senior scientists, treat failure as having positive features, enabling one to derive benefit from the experience, as long as he or she gets back on their feet (Yair 2019;Yin 2017).…”
Section: High Tolerance For Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the likelihood of failure would appear to be considered as a deterrent, inhibiting entrepreneurs from initiating new ventures. Studies on entrepreneurship have reported that tolerance of failure promotes innovation and creativity, enabling the organization to take daring moves (Kowang et al 2015). In the Israeli context, senior managers in its high-tech industry, as well as senior scientists, treat failure as having positive features, enabling one to derive benefit from the experience, as long as he or she gets back on their feet (Yair 2019;Yin 2017).…”
Section: High Tolerance For Failurementioning
confidence: 99%
“…Nevertheless, InnoCan decided to penetrate this industry by harnessing innovative technologies into the research and development process of new pharmaceutical products and significantly shortening its Time-to-Market. The team peruse their idea and took a daring move, in establishing the entity, was enabled only by the Israeli entrepreneurial "can-do" culture and its high tolerance for failure behaviour (Kowang et al 2015). This step was taken along with the perception that "even" failure has its positive aspects and can be seen as an opportunity for future learning (Yair 2019; Yin 2017).…”
Section: Innocan Pharma: a Successful Equity Campaignmentioning
confidence: 99%
“…There was a positive, significant correlation between the use of ML among leaders and academic staffs' job satisfaction level (r = 0.694, p < 0.01). With the value of r = 0.694, the strength of relationship is noted as strong (Kowang et al, 2015). This result shows that with an increase and effective use of ML within the faculty by the immediate superiors, it hugely elevates the academic staffs' job satisfaction level.…”
Section: The Usage Of Lmlmentioning
confidence: 79%
“…The second one is the Direction-giving Language (r = 0.647, p < 0.01). Based on the correlation strength interpretation by Kowang et al (2015), both Empathetic Language and Direction-giving Language have a strong relationship with academic staffs' job satisfaction level. The Meaning-making Language, on the other hand, has weak but still significant and positive correlation with the job satisfaction level (r = 0.471, p < 0.01).…”
Section: The Usage Of Lmlmentioning
confidence: 99%
“…The influence is seen from the leader behavior in consulting, delegating and assigning task, where employees are MATEC Web of Conferences 150, 05042 (2018) https://doi.org/10.1051/matecconf/201815005042 MUCET 2017 given freedom to participate in decision making process and enhance the motivation to be more innovate. They will develop innovative solution for problems or challenges faced by the organization [12]. They will also set a direction, developing a vision for the future of organization and built strategies to implement the changes needed to achieve a vision.…”
Section: Introductionmentioning
confidence: 99%